Analisis Strategic Management Pada Bebek Gembul Resto - Rio Ageng Surya Susandy; Dewi Pramesti Kusumaningrum; Maria Margarith Stely Damian Jawa (Eastasouth Institute, 2023)
The culinary industry is currently a mainstay because it provides the fastest surplus, both from the economic side of entrepreneurs, as well as from the government's income side through taxes paid. The purpose of this analytical research is to see, describe and provide recommendations related to marketing strategies in the culinary industry. This research method is a case study using SWOT analysis. The data used is primary data. While the type of research used is qualitative research. This technique explores information by using data sources from more than one point of view, such as journals, archives, articles and others. This study uses External Environmental Analysis and Internal Environmental Analysis of Bebek Gembul Resto. The results obtained from environmental analysis, SWOT analysis and strategy analysis are Bebek Gembul Resto for its strategy is good and adapts to technological developments and times. Starting from using food bloggers for promotions to frozen food innovations.